2020
DOI: 10.7717/peerj.8836
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes in the most effective pollinator of a bromeliad pollinated by bees and hummingbirds

Abstract: A generalist pollination system may be characterized through the interaction of a plant species with two or more functional groups of pollinators. The spatiotemporal variation of the most effective pollinator is the factor most frequently advocated to explain the emergence and maintenance of generalist pollination systems. There are few studies merging variation in floral visitor assemblages and the efficacy of pollination by different functional groups. Thus, there are gaps in our knowledge about the variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 77 publications
0
6
1
Order By: Relevance
“…This result indicates that the high frequency recorded for butterflies in PARNASO is probably not due to temporal variation of pollinators (Gómez et al 2010;Zhao & Huang 2013;Leal et al 2020). Besides that, several species of hummingbirds are resident and act as pollinators of dozens of species in montane Atlantic forests (Wolowski et al 2016), including our study site (Leal et al 2020). In contrast to our results, a recent study observed that hummingbirds were more important than insects at higher elevations (750-950 m a.s.l.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…This result indicates that the high frequency recorded for butterflies in PARNASO is probably not due to temporal variation of pollinators (Gómez et al 2010;Zhao & Huang 2013;Leal et al 2020). Besides that, several species of hummingbirds are resident and act as pollinators of dozens of species in montane Atlantic forests (Wolowski et al 2016), including our study site (Leal et al 2020). In contrast to our results, a recent study observed that hummingbirds were more important than insects at higher elevations (750-950 m a.s.l.…”
Section: Discussioncontrasting
confidence: 90%
“…However, different from these studies, which found hummingbirds to be the main pollinators (Castro & Araújo 2004;Almeida 2005;Ribeiro et al 2018), we found that butterflies prevailed in PARNASO over the three consecutive years of the study. This result indicates that the high frequency recorded for butterflies in PARNASO is probably not due to temporal variation of pollinators (Gómez et al 2010;Zhao & Huang 2013;Leal et al 2020). Besides that, several species of hummingbirds are resident and act as pollinators of dozens of species in montane Atlantic forests (Wolowski et al 2016), including our study site (Leal et al 2020).…”
Section: Discussionmentioning
confidence: 51%
“…Pollinator size and the frequency and manner in which the pollinators undertake floral visits, could promote differences in the contributions of sympatric pollinating species to the reproductive success of the visited plants. It is also worth noting that pollinator effectiveness can change according to season (Fishbein & Venable 1996;Rocca & Sazima 2013;Leal et al 2020)…”
Section: Reproductive Implications Due To Different Bat Pollinatorsmentioning
confidence: 99%
“…Interactions between plants and their pollinators determine the assemblage and function of communities at various temporal and spatial scales (Artz et al., 2010 ; Barônio & Torezan‐Silingardi, 2017 ; Price et al., 2005 ; Venjakob et al., 2016 ). Interactions between flowers and their pollinators are shaped by varying degrees of coevolution/coadaptation resulting in matches of floral and floral forager traits (Faegri & van der Pijl, 2013 ; Fenster et al., 2004 ; Leal et al., 2020 ; Proctor et al., 1996 ; Zych et al., 2019 ). For coadaptation to occur, the temporal and spatial dimensions of plant–pollinator interactions must be self‐consistent (Trøjelsgaard & Olesen, 2016 ; Valverde et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%